Effect of Carbon Nanotube Concentration on Thermal and Latent Heat Properties of Soy Wax-Based Composites - Bagus Irawan; Arijanto Arijanto; Dini Cahyandari; Muhammad Subri; Gery Salsabil; Febiyanto Febiyanto (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Phase Change Materials (PCMs) absorb and release thermal energy during phase transitions, making them valuable for applications such as temperature regulation, energy storage, and passive heating or cooling systems. Soy wax, a natural PCM, is an attractive candidate due to its abundance and biodegradability; however, its low thermal conductivity limits its efficiency in energy storage applications. To address this limitation, this study investigates the incorporation of carbon nanotubes (CNTs) into a soy wax matrix to enhance thermal performance. Soy wax-CNT composites were synthesized using a melt-mixing method, with CNTs dispersed at varying concentrations (0.5%, 1%, and 3% by weight). Differential Scanning Calorimetry (DSC) was employed to analyze phase transition characteristics. The results demonstrate that the addition of CNTs significantly improved the thermal conductivity of soy wax, increasing from 0.21 W/m·K (pure soy wax) to 0.36 W/m·K at 0.5% CNT loading, representing a 71% enhancement. The latent heat of fusion peaked at 22.00 J/g at this optimal CNT concentration, indicating improved energy storage capacity. Furthermore, thermal cycling tests confirmed enhanced stability, with minimal degradation after multiple heating and cooling cycles. These findings highlight the potential of soy wax-CNT composites as improved PCMs for thermal energy storage applications, offering enhanced conductivity, higher latent heat, and improved thermal cycle durability.